PENERAPAN ALGORITMA KNUTH MORRIS PRATT PADA APLIKASI PENCARIAN BERKAS SHIPMENT BERBASIS WEB ( STUDI KASUS DI PT YEC SEMARANG) - Nurul Khasanah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
Abstract PT. Yudhanusa Ekspresindo Caraka has a lot of transaction data used in the completion of both export and import shipments. The current system that has been running is manual searching files by searching for the files in the physical form on the file cabinets and looking for a pdf file contained in an email attachment. With the searching system application is developed with the programming language ASP.net MVC and SQLite database by applying the Knuth-Morris-Pratt algorithm. Based on the effectiveness of the test results, it can be concluded that the effectiveness of the new system is much larger than the old system, which amounts to 85.00%. As for the old system only amounted to 45.00%. This shows that the new system has been better and more effective. Keywords: Information system, file search, Knuth Morris Pratt algorithm, Shipment. The essence of PT. Yudhanusa Ekspresindo Caraka has a lot of transaction data used in the completion of an export or import shipment. The system that has been running in the search for files is still manual by searching for files in physical form in the file cabinet or looking for pdf attachments contained in the email. The file search system was developed with the ASP.net MVC programming language and SQLite database by applying the Knuth Morris Pratt algorithm. From the results of the effectiveness test, it can be concluded that the effectiveness of the new system is far greater than the old system, which is 85.00%. Whereas the old system was only 45.00%. This shows that the new system is better and more effective.